Incidence of injuries in professional snow sports: A systematic review and meta-analysis - Xue-Lei Fu; Lin Du; Yi-Ping Song; Hong-Lin Chen; Wang-Qin Shen (Elsevier, 2022)
Purpose: The study aimed to conduct a comprehensive systematic review and meta-analysis of injury incidence in professional skiers and snowboarders. Methods: We systematically searched PubMed, Web of Science, and MEDLINE for studies on injury incidence published from inception to April 2020. Injury data were extracted, alongside information on injury location, severity, type, cause, and sport discipline. Incidence of injuries was presented per 1000 athlete-days, with 95% confidence intervals (95%CIs). Results: The search identified 462 articles, and 22 were included in our review. The overall incidence of injuries among professional skiers and snowboarders was 3.49 per 1000 athlete-days (95%CI: 2.97-4.01). Lower extremity had the highest injury incidence (1.54 per 1000 athlete-days, 95%CI: 1.24-1.84). Incidence rates of slight, mild, moderate, and severe injuries were 0.26, 0.31, 0.57, and 0.59 per 1000 athlete-days, respectively. Contusion had the highest incidence rate (1.82 per 1000 athlete-days, 95%CI: 1.01-2.63). The most common cause of injury was contact trauma (3.20 per 1000 athlete-days, 95%CI: 1.32-5.08). Freestyle skiing had the highest incidence rate (6.83 per 1000 athlete-days, 95%CI: 4.00-9.66), and Nordic skiing had the lowest rate (2.70 per 1000 athlete-days, 95%CI: 1.94-3.46). Conclusion: Professional skiers and snowboarders have a substantial risk of sustaining injuries. Our findings can be used to inform the planning and provision of healthcare for elite participants in different snow sports.